USE OF ASSOCIATIVE CARDS AS A TOOL OF PSYCHOTHERAPY TREATMENT OF PERSONS WITH IDENTITY CRISIS - . Dmitrieva, Nataliya V. Dmitrieva; Levina, Larisa V. (Revista Inclusiones, 2021)
Dealing with everyday psychological problems and difficulties, especially those resulting from an identity crisis, requires effective tools to monitor personal transformations. Associative cards, which contain metaphorical images, are among such tools of art therapy, but using them in the therapy of identity crises is a new research area. The research aims to investigate the existing practice of using associative cards for the psychotherapy treatment of persons with an identity crisis. There were studied 283 individuals with an identity crisis (persons with antisocial behavior, asocial, and selfdestructive behavior), who were compared to 283 persons without manifestations of crisis. Psychodiagnostic techniques determined psychological features of individuals with an identity crisis, which allowed identifying factors for their deviant behavior and specifying approaches to using associative cards in their psychotherapy. Associative cards contribute to dealing with emotional states, controlling anxiety, recognising the motivation for actions, making decisions, taking personal responsibility, and maintaining independent attitude.